2023
DOI: 10.21142/2523-2754-1102-2023-156
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenesis imperfecta. Case report

Nicole Alessandra Herrera-Rojas,
Guido Alberto Perona-Miguel de Priego

Abstract: The main origin of amelogenesis imperfecta (AI) is a genetic alteration inherited by a family member which affects the dental enamel of the teeth of a person with this condition in various ways. The present clinical case from the Teaching Dental Clinic of the Peruvian University Cayetano Heredia is of a 6-year 5-month-old male child who came to the dental office accompanied by his father and 8-year-old sister, diagnosed with the same AI condition. The comprehensive treatment proposed for this patient was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Genetics involved in the development of AI have not been identified; however, 10 genes have been associated with AI and are found in molecular diagnosis in most cases. In the past, children with AI were only given oral hygiene instructions and fluoride applications, with treatment initiated after the complete eruption of permanent teeth [ 19 , 20 ]. Contemporary approaches involve restorative and prosthetic treatments, along with strict dietary and oral hygiene instructions, serving as the primary line of treatment for AI in both children and adults.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetics involved in the development of AI have not been identified; however, 10 genes have been associated with AI and are found in molecular diagnosis in most cases. In the past, children with AI were only given oral hygiene instructions and fluoride applications, with treatment initiated after the complete eruption of permanent teeth [ 19 , 20 ]. Contemporary approaches involve restorative and prosthetic treatments, along with strict dietary and oral hygiene instructions, serving as the primary line of treatment for AI in both children and adults.…”
Section: Reviewmentioning
confidence: 99%
“…The final treatment commences as soon as the clinical height of the crown is established and the pulp tissue has receded. Full-mouth rehabilitation with a multidisciplinary approach is advisable at this stage, incorporating prosthodontic, endodontic, restorative, periodontic, and orthodontic management [ 19 , 20 , 21 , 26 , 28 , 33 ]. Some studies have suggested orthognathic surgery for abnormal skeletal growth.…”
Section: Reviewmentioning
confidence: 99%